Reliability of power output during eccentric sprint cycling - Brughelli, M.; Van Leemputte, M. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to determine the reliability of power outputs during maximal intensity eccentric cycling over short durations (i.e., eccentric sprint cycling) on a "motor-driven" isokinetic ergometer. Fourteen physically active male subjects performed isokinetic eccentric cycling sprints at 40, 60, 80, 100, and 120 revolutions per minute (rpm) on 4 separate occasions (T1-T4). Each sprint lasted for 6 seconds, and absolute measures of mean power (MP) and peak power (PP) per revolution were recorded. Significant increases in MP and PP were observed between T1 and subsequent trials, but no significant differences were identified between T2, T3, and T4. The coefficient of variation (CV) and intraclass correlation coefficient (ICC) were calculated to reflect within-subject and between-session reliability of MP and PP at each cadence. The CV improved to below 10% for cadences of 60, 80, 100, and 120 rpm between T3 and T4, and the majority of ICC values improved to above 0.90. The remaining ICC values remained in the moderate range between T3 and T4 (i.e., 0.82-0.89). Coefficient of variation and ICC values for the 40 rpm cadence remained at unacceptable levels throughout the 4 trials and thus should be avoided in future investigations. The results of this study indicate that reliable power outputs may be obtained after 2 familiarization sessions during eccentric sprint cycling at cadences ranging from 60 to 120 rpm.